2009
DOI: 10.1097/fpc.0b013e32832e042e
|View full text |Cite
|
Sign up to set email alerts
|

Very important pharmacogene summary: sulfotransferase 1A1

Abstract: Cytosolic sulfotransferase 1A subfamily members catalyze the sulfate conjugation of phenolic compounds including steroid hormones, catecholamines, and phenolic drugs and also participate in the bioactivation of procarcinogens (reviewed in Ref.[1]). The endogenous cosubstrate 3 0 -phosphoadenosine 5 0 -phosphate (PAPS) acts as the sulfate donor. Sulfotransferase 1A1 (SULT1A1) metabolizes several phenolic substrates including simple phenolic compounds (4-nitrophenol, which is used as a probe substrate, [2]); dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
10
0
2
Order By: Relevance
“…Previous studies have demonstrated that there is a high interindividual variability in SULT enzyme expression and activity, which has been attributed to both environmental and genetic factors . For example, SULT1A1 exhibits over 50‐fold variations in enzyme activity, associated in part with single nucleotide polymorphisms and copy number variations . Thus, it is important to identify the contributions of the individual SULT isoforms to the sulfation of MF stereoisomers and the potential for pharmacogenetic differences in bioavailability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have demonstrated that there is a high interindividual variability in SULT enzyme expression and activity, which has been attributed to both environmental and genetic factors . For example, SULT1A1 exhibits over 50‐fold variations in enzyme activity, associated in part with single nucleotide polymorphisms and copy number variations . Thus, it is important to identify the contributions of the individual SULT isoforms to the sulfation of MF stereoisomers and the potential for pharmacogenetic differences in bioavailability.…”
Section: Discussionsupporting
confidence: 91%
“…14 For example, SULT1A1 exhibits over 50-fold variations in enzyme activity, associated in part with single nucleotide polymorphisms and copy number variations. 15 Thus, it is important to identify the contributions of the individual SULT isoforms to the sulfation of MF stereoisomers and the potential for pharmacogenetic differences in bioavailability. The data from this study demonstrate that the sulfation of MF stereoisomers is mediated by SULT1A1*1, SULT1A1*2, SULT1A3, and SULT1E1 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been established that tamoxifen and its metabolites undergo phase II conjugation reactions including glucuronidation and sulfation, few studies have examined the role of phase II sulfotransferase enzymes (SULTs) in TAM metabolism. Given that 4-OH-TAM and endoxifen are known substrates of SULT1A1 [5 and 6, respectively], different SULT enzyme activity levels could markedly influence the efficacy of TAM [5].…”
Section: Introductionmentioning
confidence: 99%
“…Männliche Ratten weisen eine deutliche höhere Sulfotransferaseaktivität auf als weibliche Ratten und Ratten eine höhe-re als Mäuse [28]. Die Aktivität der humanen Sulfotransferase 1A1 (SULT1A1) variiert um eine Vielfaches zwischen Individuen, bedingt unter anderem durch Einzelnukleotid-Polymorphismen (SNP) und Kopienanzahlvariationen (CNV) [29].…”
Section: Geruchswahrnehmungunclassified